The application potential of net zero energy building using rooftop photovoltaics case study of apartments in Gorontalo Province - Djafar, Abdi Gunawan; Pratiwi, Niniek; Mohamad, Yasin; Zhai, Zhiqiang John (Institute of Advanced Engineering and Science, 2025)
Gorontalo Province is one of the developing regions in Indonesia. The province has been actively building apartments since 2009. The construction increases population density and energy use intensity. Consequently, demand for electricity power rises. Renewable energy such as rooftop photovoltaics has the potential as a power source for the apartments, considering the abundant solar radiation in Gorontalo which is located near the equator line. Three apartments representing three levels of the inhabitant’s income are selected as study case for the application of photovoltaic (PV) on roof to achive net zero energy building. Simulation of PV energy to power the buildings is conducted using photovoltaic geographical information system (PVGIS). By utilizing monthly electrical bill data, it is found that PV on roof is sufficient to cover the building energy demand and achieve net zero energy building (NZEB). However, there is uncertainty of the fluctuation of energy demand due to the tenant’s energy consumption behaviour. The consumption intensity is limited only by the installed power on each apartment unit. PV on roof alone is unable to provide the need if it is employed to power the unit to the maximum extent.